Eco-friendly management of cardamom root grub (Basilepta fulvicorne Jacoby) through entomopathogenic nematodes - S. DEVASAHAYAM and T.K. JACOB, RASHID PERVEZ*, SANTHOSH J. EAPEN (Indian Phytopathology, 2016)
Studies on the infective juvenile (IJs) of entomopathogenic nematodes attachment, penetration into root grub and infectivity of eight native EPNs namely, Heterorhabditis sp. (IISR-EPN 01), Steinernema sp. (IISR-EPN 02), S. ramanai (IISR-EPN 03), S. carpocapsae (IISR-EPN 06), Oscheius gingeri (IISR-EPN 07) and Oscheius spp. (IISR-EPN 04, 05, and 08) were tested against cardamom root grub. Among the tested EPNs, maximum number of O. gingeri (IISR-EPN 07) IJs attached, followed by Heterorhabditis sp. (IISR-EPN 01) after 3 h of inoculation. Maximum number of Heterorhabditis sp. (IISR-EPN 01) IJs penetrate into grub, followed by O. gingeri (IISR-EPN 07). The lowest rate of penetration was found in the Oscheius sp. (IISR-EPN 05). In case of infectivity of EPNs, Heterorhabditis sp. (IISR-EPN 01) and O. gingeri (IISR-EPN 07) caused 100 % mortality to root grub, followed by S. ramanai (IISR-EPN 03) (83%). Whereas, Steinernema sp. (IISR-EPN 02), S. carpocapsae (IISR-EPN 06) and Oscheius sp. (IISR-EPN 08) brought about 67% mortality. However, Oscheius spp. (IISR-EPN 04 and 05) kill only 50% root grub after 72 h. Infectivity of these EPN against cardamom root grub is being reported for the first time. This opens a new non chemical option for management of insect pests of cardamom.